1994
DOI: 10.1161/01.res.74.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of reperfusion-induced leukocyte adhesion and vascular protein leakage.

Abstract: The adherence and emigration of leukocytes have been implicated as a rate-limiting step in the microvascular dysfunction associated with reperfusion of ischemic tissues. The objective of the present study was to define the relation between leukocyte-endothelial cell adhesion and albumin leakage in rat mesenteric venules exposed to ischemia and reperfusion (I/R). Leukocyte adherence and emigration as well as albumin extravasation were monitored in single post-capillary venules using intravital fluorescence micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
159
0
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(179 citation statements)
references
References 32 publications
3
159
0
17
Order By: Relevance
“…Previous reports have shown that leukocyte-endothelial interactions can trigger endothelial cell adherens and tight junction disorganization, 21,22 as well as increases in vascular permeability. 23 Others have demonstrated that VEGF has direct effects on vascular permeability. 24 In vitro studies have documented changes in electrical resistance and hydraulic conductivity in isolated endothelial monolayers treated with VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that leukocyte-endothelial interactions can trigger endothelial cell adherens and tight junction disorganization, 21,22 as well as increases in vascular permeability. 23 Others have demonstrated that VEGF has direct effects on vascular permeability. 24 In vitro studies have documented changes in electrical resistance and hydraulic conductivity in isolated endothelial monolayers treated with VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…11 As reperfusion injury ensues, endothelial disruption, expression of adhesion molecules, and leukocyte infiltration with subsequent activation of the entire inflammatory armamentarium occurs. 11,18 Some investigators have suggested that neutrophil infiltration and cumulative free radical release are the most important mediators of I/R injury. 19,20 Tacrolimus, as an immunomodulatory agent, is likely to have a profound effect on the inflammation avenue of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although XOD derived from endothelial cells contributes to the initial oxidant stress, ROS derived from adherent leukocytes may provide the more substantial and prolonged oxidant burst that occurs in IR injury (14). There is also evidence that leukocyte-endothelial binding mediated by adhesion molecules and subsequent leukocyte emigration into tissues is proportional to the degree of endothelial-cell barrier dysfunction, further supporting a primary role for adhesion molecules as a central regulator of local and distant IR-related injury (25). Taken together, these findings add to the growing evidence suggesting that ROS production and WBC adhesion events are interconnected (15,31).…”
Section: Postcapillary Venular Endothelial Cells Are Especially Suscementioning
confidence: 99%
“…Others have previously documented the importance of WBC adhesion in IR injury (22). Furthermore, monoclonal antibodies against ICAM-1 or against CD11/18 on neutrophils have been shown to reduce WBC adhesion and attenuate the increased vascular permeability during IR (25,36).…”
Section: Postcapillary Venular Endothelial Cells Are Especially Suscementioning
confidence: 99%